2021
DOI: 10.1186/s13059-021-02513-w
|View full text |Cite|
|
Sign up to set email alerts
|

Surfaceome CRISPR screen identifies OLFML3 as a rhinovirus-inducible IFN antagonist

Abstract: Background Rhinoviruses (RVs) cause more than half of common colds and, in some cases, more severe diseases. Functional genomics analyses of RVs using siRNA or genome-wide CRISPR screen uncovered a limited set of host factors, few of which have proven clinical relevance. Results Herein, we systematically compare genome-wide CRISPR screen and surface protein-focused CRISPR screen, referred to as surfaceome CRISPR screen, for their efficiencies in id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…With the above criteria, the CRISPR-Surfaceome website contains 216,530 sgRNAs spanning the 18,421 genes in the genome with an average of 12 sgRNAs per gene. The 1,344 surface proteins are defined using the information from a mass spectrometry database [31] as previously described [23] . Gene ontology analysis of the cellular components of the surface proteins shows that the majority is located on plasma membrane and/or extracellular matrix, rather than intracellular membranes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the above criteria, the CRISPR-Surfaceome website contains 216,530 sgRNAs spanning the 18,421 genes in the genome with an average of 12 sgRNAs per gene. The 1,344 surface proteins are defined using the information from a mass spectrometry database [31] as previously described [23] . Gene ontology analysis of the cellular components of the surface proteins shows that the majority is located on plasma membrane and/or extracellular matrix, rather than intracellular membranes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RVs were produced as previously described [23] . For RV infection, H1-Hela cells were seeded on to 96- or 12-well plates with a density of 2.0 × 10 4 cells per well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, SETD3 interacts with viral 2A protease regardless of its protease activity, and these interactions are required for viral replication, suggesting that the 2A protease has a previously undocumented pro-viral role unrelated to its protease activity ( Diep et al, 2019 ). Moreover, CRISPR-Cas9 screens identified OLFML3 which support rhinovirus replication via suppression of the interferon response and multiple host proteins (e.g., MGAT5 and COG1) required for EV-D68 infection ( Kim et al, 2017 ; Mei et al, 2021 ).…”
Section: Crispr-cas9 As a Genome-wide Genetic Screening Tool For Stud...mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author affiliations presented in additional file 1 . The additional file has been updated and published in this correction.…”
mentioning
confidence: 99%